ANALISIS PROGRAM PENDIDIKAN KESETARAAN PADA PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DALAM PERSPEKTIF TEORI STRUKTURAL FUNGSIONAL TALCOTT PARSONS - Detty adithya ayunda putri tandjung; Delfira Rahmatia Utami; Novia Nurul Hidayanti; Muhammad Hafiz; Rudy Kurniawan (STKIP Subang, 2026)
This study aims to analyze the Equivalency Education Program within Community Learning Activity Centers (PKBM - Pusat Kegiatan Belajar Masyarakat) through the perspective of Talcott Parsons' Structural Functionalism Theory. Employing a descriptive qualitative research method with a literature review data collection technique, this study examines data from various relevant sources since 2020. The results of the analysis indicate that PKBMs function as a crucial subsystem in maintaining the equilibrium of the social system, particularly in addressing issues of school dropouts and disparities in educational access. The Equivalency Programs (Package A, B, and C) within PKBMs fulfill the four functional imperatives within Parsons' AGIL framework (Adaptation, Goal Attainment, Integration, and Latency). Adaptation is realized through adjustments to fill educational access gaps for vulnerable populations and empower uncertified human resources. Goal Attainment is achieved by reducing the dropout rate and providing inclusive non-formal education services. Integration functions as an instrument for unifying marginalized groups through the recognition of equivalency certificates and the strengthening of social solidarity. Meanwhile, Latency seeks to maintain system stability by revitalizing the spirit of learning and reproducing socio-cultural values. The total number of PKBM equivalency education institutions in Indonesia is 25,795.